Early Childhood Education Leadership in Times of Crisis International Studies During the COVID-19 Pandemic - Fonsén, Elina; Ahtiainen, Raisa; Heikkinen, Kirsi-Marja; Heikonen, Lauri; Strehmel, Petra; Tamir, Emanuel (Verlag Barbara Budrich, 2023)
The COVID-19 pandemic has dramatically affected all aspects of professional and private life worldwide, including the field of early childhood education and care (ECE). This volume sheds light on leadership in ECE: How did leaders experience the challenges they were facing and what coping strategies did they apply in order to deal with the changes in everyday life and practices in ECE centres? Authors from twelve countries present empirical findings gaining information on different crisis management mechanisms in ECE systems around the world.